Some Integral Type Fixed Point Theorems for Non-Self-Mappings Satisfying Generalized (ψ, φ)-Weak Contractive Conditions in Symmetric Spaces. (7th April 2014) - Kutbi, Marwan Amin; Imdad, Mohammad; Chauhan, Sunny; Sintunavarat, Wutiphol
Abstract : The aim of this paper is to obtain some new integral type fixed point theorems for nonself weakly compatible mappings in symmetric spaces satisfying generalized ( ψ, φ ) -contractive conditions employing the common limit range property. We furnish some interesting examples which support our main theorems. Our results generalize and extend some recent results contained in Imdad et al. (2013) to symmetric spaces. Consequently, a host of metrical common fixed theorems are generalized and improved. In the process, we also derive a fixed point theorem for four finite families of mappings which can be utilized to derive common fixed point theorems involving any number of finite mappings.